Partisipasi Politik Masyarakat pada Pilkada Ulang Kota Pangkalpinang dan Kabupaten Bangka Tahun 2025: Perspektif Participatory Democracy - Annaml Salma Jaffis; Tata Dwi Syintia; Nadira Ramadani; Serlyani Rizky Octaria; Suci Aprilia (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The re-run local elections in Pangkalpinang City and Bangka Regency following the victory of the blank box option in the 2024 simultaneous local elections provide an important context for understanding contemporary patterns of political participation in Indonesia. This study explores the forms, levels, and determinants of political participation through a qualitative multiple-case study comparing urban and rural communities. Data were collected through in-depth interviews with 14 informants, complemented by document analysis and literature review, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that political participation extends beyond voting behavior to include involvement in election campaigns, political discussions, and electoral oversight activities. Participation levels are shaped by the interaction of structural, institutional, and cultural factors. Structural determinants include educational attainment, economic conditions, access to information, and social media utilization. Institutional factors encompass the performance of electoral management bodies, political socialization processes, and public trust in political institutions. Cultural influences involve political values, community leadership, and patronage networks. The study further reveals distinct participation patterns between urban and rural communities, with urban voters tending to demonstrate more rational and autonomous political behavior, while rural participation remains strongly influenced by social relations and local leadership structures.